PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA KELAS VII SMP NEGERI 13 KOTA BENGKULU - Sulastri Sinaga; I Wayan Dharmayana; Anni Suprapti (UNIVERSITAS BENGKULU, 2024)
This research aimed to determine the effect of group guidance services using role playing techniques to increase the self-confidence of class VII students at SMP Negeri 13 Bengkulu City. The method used in this research is an experimental method with a one group pre-test and post-test design. The population in this study was 31 students, with a sample of 11 students determined using purposive sampling techniques. The data collection technique in this research uses a student self-confidence questionnaire instrument with a Likert scale model. The data analysis technique uses the t test (paired sample t-test), which shows the value of t = -8.830 (P< 0,05). This means that there is a significant influence of group guidance services using role playing techniques on students self-confidence. Keywords: role playing technique group guidance services, student self-confidence